(3QSGdI aj GdcdGe Ydi eSFdI GdZjes - (3eMeO Hf GdUGdM GdYGHO YeGO CMeO Hf YHO GdgGOj GdebOTj GdMfHdj, CHh YHO Gddgs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO aUd ai GdcdGe Ydi eSFdI GdZje eNJUQkG hHjGf GdENJdGa ajgG s
(3BNQgG (B:s
(3dG jOd Ydi GdhLhH Yf HYVge de jcf bhdg MLg SeY eNGdaI ZjQg heY eNGdaI GdCMGOjK GdUMjMI GdUQjMg hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs